Degradation of Xylan to d-Xylose by Recombinant Saccharomyces cerevisiae Coexpressing the Aspergillus niger β-Xylosidase (xlnD) and the Trichoderma reesei Xylanase II (xyn2) Genes - La Grange, D. C. (American Society for Microbiology, 2001)
The β-xylosidase-encoding xlnD gene of Aspergillus niger 90196 was amplified by the PCR technique from first-strand cDNA synthesized on mRNA isolated from the fungus. The nucleotide sequence of the cDNA fragment was verified to contain a 2,412-bp open reading frame that encodes a 804-amino-acid propeptide. The 778-amino-acid mature protein, with a putative molecular mass of 85.1 kDa, was fused in frame with the Saccharomyces cerevisiae mating factor α1 signal peptide (MFα1(s)) to ensure correct posttranslational processing in yeast. The fusion protein was designated Xlo2. The recombinant β-xylosidase showed optimum activity at 60°C and pH 3.2 and optimum stability at 50°C. The K(i(app)) value for d-xylose and xylobiose for the recombinant β-xylosidase was determined to be 8.33 and 6.41 mM, respectively. The XLO2 fusion gene and the XYN2 β-xylanase gene from Trichoderma reesei, located on URA3-based multicopy shuttle vectors, were successfully expressed and coexpressed in the yeast Saccharomyces cerevisiae under the control of the alcohol dehydrogenase II gene (ADH2) promoter and terminator. These recombinant S. cerevisiae strains produced 1,577 nkat/ml of β-xylanase activity when expressing only the β-xylanase and 860 nkat/ml when coexpressing the β-xylanase with the β-xylosidase. The maximum β-xylosidase activity was 5.3 nkat/ml when expressed on its own and 3.5 nkat/ml when coexpressed with the β-xylanase. Coproduction of the β-xylanase and β-xylosidase enabled S. cerevisiae to degrade birchwood xylan to d-xylose.